Presence of Clostridioides difficile and multidrug-resistant healthcare-associated pathogens in stool specimens from hospitalized patients in the USA. Issue 1 (September 2020) - Tickler, I.A.; dela Cruz, C.M.; Obradovich, A.E.; Goering, R.V.; Dewell, S.; Le, V.M.; Tenover, F.C.; ,; Anderson, J.; Banaei, N.; Bankowski, M.; Dill, J.L.; et al.
Summary: Background: Healthcare-associated infections (HCAIs) continue to be a major cause of morbidity and mortality. Many HCAI pathogens, including multidrug-resistant organisms (MDROs), colonize the gastrointestinal tract. Aim: To determine the frequency of MDRO carriage in patients who do and do not harbour toxigenic Clostridioides difficile in their stools. Methods: Stool specimens received from nine US laboratories were cultured using media selective for C. difficile, Staphylococcus aureus, vancomycin-resistant enterococci (VRE), and carbapenem-resistant Gram-negative organisms (CROs). Specimens and isolates were also tested by polymerase chain reaction (PCR). Bacterial isolates underwent susceptibility testing and genotyping. Findings: Among 363 specimens, 175 yielded toxigenic C. difficile isolates spanning 27 PCR ribotypes . C. difficile (TCD + ) stools harboured an additional 28 organisms, including six CROs (3.4%), of which two (1.1%) were carbapenemase-producing organisms (CPOs), 19 VRE (10.9%), and three meticillin-resistant S . aureus isolates (MRSA, 1.7 %). Stools that were culture negative for toxigenic C. difficile (TCD – ) yielded 26 organisms, including four CROs (2.1%), 20 VRE (10.6), and two MRSA (1.1%). Excluding C. difficile, no significant differences were seen in the rates of the MDROs between TCD + and TCD – specimens. Conclusion: Overall, 15.4% of the TCD + stools and 11.2% of the TCD – stools carried at least one non- C. difficile MDRO pathogen, indicating that multiple MDROs may be present in the gastrointestinal tracts of patients, including those that harbour C. difficile .